Changes in insulin resistance and other metabolic parameters during home quarantine amid the COVID-19 pandemic among the general population - Zhang, Yuting; Chen, Wenting; Ran, Lijian; Wang, Jing; Xia, Jie; Li, Shilian; Mao, Qing; Chen, Zongtao; Liu, Huimin (Frontiers in Nutrition, 2025)
BackgroundThis study aims to investigate the impact of home quarantine on insulin resistance and other metabolic parameters in general populations through the changes in metabolic profile, especially Triglyceride/Glucose (TyG).MethodsThis study included participants who underwent two health checkups at the Health Management Center of the First Affiliated Hospital of the Army Medical University, before and after home quarantine, between December 2021 and February 2023. The home quarantine policy in the Chongqing area was executed between August 2022 and December 2022. Triglyceride/Glucose (TyG), TyG-body mass index (TyG-BMI), and TyG-waist circumference (TyG-WC) were calculated.ResultsA total of 19,957 cases were screened, and 2,473 participants (mean age: 39.35 ± 10.36 years, 69.8% female) were included for the final analysis. Compared to before home quarantine, the TyG (6.80 ± 0.58 vs. 6.83 ± 0.58, p < 0.001), TyG-BMI (158.30 ± 31.92 vs. 159.48 ± 31.73, p < 0.001), and TyG-WC (533.53 ± 103.15 vs. 535.78 ± 103.65, p = 0.039) increased significantly after the home quarantine. Besides, glucose, lymphocyte, and platelet decreased significantly while BMI, systolic blood pressure, diastolic blood pressure, pulse, total cholesterol, triglyceride, high-density lipoprotein, low-density lipoprotein, uric acid, red blood cell, and monocyte also increased significantly after home quarantine (all p < 0.05).ConclusionHome quarantine might pose a potential negative impact on insulin resistance risk, indicating that insulin resistance and other metabolic health parameters during the home quarantine period should be monitored regularly.